Exploring the Registers of Identity Research. (July 2017) - Corlett, Sandra; McInnes, Peter; Coupland, Christine; Sheep, Mathew
Abstract: As the lead, introductory, contribution to this special issue 'Exploring Registers of Identity Research', this paper offers a view of three different 'registers' that might be seen to characterize identity research and which feature, to a greater or lesser extent, in the selected papers. First, the paper offers a means to understand the different theoretical traditions used to explain what constitutes identity and how it might be known. Second, it considers the relationship between different levels of identity – individual, group, professional, organizational and societal. Third, it reviews the methodologies used to understand identities and examines key theoretical assumptions which feature in academic debates, and in the selected papers, around identity theorizing. Drawing on the papers included in this special issue we offer a framework as a heuristic device that might guide scholars looking to enter the field of identity research and enable those already familiar with particular theoretical traditions, levels or methods to explore possibilities for extending their research. As an enticement to tackle the challenges extension across‐registers can present, we again turn to the special issue articles to examine – through a series of 'gets' – the different tactics authors might use to access the rich potential offered by cross‐fertilization between registers. Our contribution then lies in advancing the potential for dialogue between registers of identity research.